Non linear filtration of phase manipulated signals having spread spectrum under condition of structural indefiniteness - Andonov, Antonio; Dimkin, Petar; Iliev, Filip (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper discusses an approach about non linear filtration of phase manipulated signals hav-ing spread spectrum under condition of structural indefiniteness.